Faktor-Faktor yang Berpengaruh terhadap Persepsi Mahasiswa Tentang Etika Profesi Akuntan - Orisu, Virlitha G. B.; Mokodompit, Mona Permatasari; Wuriasih, Anik (Fakultas Ekonomi dan Bisnis Universitas Papua, 2021)
ABSTRACT This study aims to empirically examine the influence of emotional intelligence, intellectual intelligence and love of money toward student’s perceptions on accountant professional ethics. Research data were collected by giving questionnaires to 91 accounting students of Economic and Business Faculty at Universitas Papua. The number of respondents is determined using saturated sampling technique. The data were then analyzed by using multiple linear regression analysis. The results of this study shows that from the three factors examined only intellectual intelligence that has influence towards student’s perception on accountant professional ethics. Whereas emotional intelligence and love of money have no influence toward student’s perception on accountant professional ethics. Keywords: Emotional Intelligence, Intellectual Intelligence, Love of Money, Student’s Perception, Accountant Profesional Ethics ABSTRAK Penelitian ini bertujuan untuk menguji secara empiris pengaruh kecerdasan emosional, kecerdasan intelektual dan love of money terhadap persepsi mahasiswa tentang etika profesi akuntan. Data penelitian ini diperoleh dengan membagikan kuisioner kepada 91 mahasiswa akuntansi di Fakultas Ekonomi dan Bisnis Universitas Papua. Jumlah responden yang dijadikan sampel tersebut ditentukan dengan menggunakan teknik sampling jenuh, Data kemudian dianalisis menggunakan analisis regresi linear berganda. Hasil penelitian ini menunjukkan bahwa dari tiga faktor yang diteliti hanya kecerdasan intelektual yang berpengaruh terhadap persepsi mahasiswa tentang etika profesi akuntan. Sedangkan kecerdasan emosional dan love of money tidak berpengaruh terhadap persepsi mahasiswa tentang etika profesi akuntan. Kata Kunci: Kecerdasan Emosional, Kecerdasan Intelektual, Love of Money, Persepsi Mahasiswa, Etika Profesi Akuntan